METTL5 in physiology and pathology: mechanisms and implications - Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2025)
METTL5, in complex with TRMT112, catalyzes N6-methyladenosine (m6A) at A1832 of 18S rRNA, acting as a novel regulator of translational control. This modification within the ribosomal decoding center modulates ribosome assembly and selective mRNA translation. Physiologically, METTL5 is required for embryonic and neural development, stem cell fate, spermatogenesis, and cardiac function. Aberrant expression has been reported in multiple cancers, where it correlates with poor prognosis. Mechanistically, METTL5 drives proliferation, metastasis, and chemoresistance by promoting oncogenic translation, reprogramming metabolism, regulating ferroptosis, and shaping the immune microenvironment. Cooperation with m6A readers, including IGF2BP and YTHDF proteins, contributes to these effects. Targeting METTL5 shows therapeutic promise, with compounds such as salvianolic acid C and scutellarin demonstrating inhibitory activity. In this review, we summarize the molecular characteristics, physiological roles, and pathological functions of METTL5, highlight its mechanisms in tumorigenesis and immunity, and discuss its potential as a biomarker and therapeutic target.